Proposed laboratory investigation into electroosmotic dewatering of mine tailings - Vander Vis, Kimberly Ann, author; Bareither, Christopher, advisor; Scalia, Joseph, advisor; Sanford, William, committee member (Colorado State University. Libraries, 2020)
Geotechnical concerns of tailings storage facilities (TSFs) often depend on the water content of the tailings. Tailings with low hydraulic conductivity often have high-water contents with low undrained shear strength at the time of mine closure which limits the ability to close the TSF. The purpose of this study is to explore undrained shear strength gain in surficial mine tailings using electroosmotic dewatering (EOD) to help promote closure and reclamation of TSFs. Electroosmotic dewatering uses electrodes to apply an electrical direct current to induce flow through a porous medium. An experiment was developed to assess the effectiveness of dewatering methods at bench-scale to increase undrained shear strength of tailings via three different methods: EOD, surcharge consolidation, and evaporation only. The proposed research will evaluate if EOD (1) increases undrained shear strength of saturated surficial mine tailings more rapidly and (2) increases undrained shear strength as a function of depth more effectively, compared to the other techniques. Factors that influence EOD were preliminarily evaluated and include electrodes used, pore fluid chemistry, degree of saturation, voltage gradient and electrode configuration. Additionally, electroosmotic dewatering of mine tailings has not been implemented on a large-scale possibly due to lack of developed procedure, difficult water removal, and lack of a commercially available EOD unit. A goal of the proposed research plan is to develop field-scale implementation methods and water removal techniques via a moisture wicking synthetic capillary drain unit to be coupled with electroosmotic dewatering (i.e., EO-Plant) for field-scale applications.
Keywords: electroosmotic; dewatering; tailings